2002
DOI: 10.1042/bj3620539
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of 7-methylguanosine 5′-triphosphate (m7GTP)- and P1-7-methylguanosine-P3-adenosine-5′,5′-triphosphate (m7GpppA)-bound human full-length eukaryotic initiation factor 4E: biological importance of the C-terminal flexible region

Abstract: The crystal structures of the full-length human eukaryotic initiation factor (eIF) 4E complexed with two mRNA cap analogues [7-methylguanosine 5′-triphosphate (m7GTP) and P1-7-methylguanosine-P3-adenosine-5′,5′-triphosphate (m7GpppA)] were determined at 2.0Å resolution (where 1Å = 0.1nm). The flexibility of the C-terminal loop region of eIF4E complexed with m7GTP was significantly reduced when complexed with m7GpppA, suggesting the importance of the second nucleotide in the mRNA cap structure for the biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Recombinant eIF4E protein for crystallographic studies was prepared as previously reported. 20,37 In brief, the full length human eIF4E was cloned into vector pET101 with an N-terminal FLAG 6xHis tag followed by an rTEV cleavage site. The protein was expressed in E. coli and purified through a m7-GTP-sepharose column.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Recombinant eIF4E protein for crystallographic studies was prepared as previously reported. 20,37 In brief, the full length human eIF4E was cloned into vector pET101 with an N-terminal FLAG 6xHis tag followed by an rTEV cleavage site. The protein was expressed in E. coli and purified through a m7-GTP-sepharose column.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…In the N-terminal end, sequences are variable between different organisms, but this end does not seem to be involved in the initiation to translation function. The tertiary structure was characterized in mice, men, yeast, and wheat (Monzingo et al, 2007;Tomoo et al, 2002). This structure is composed of eight antiparallel β strands and three helices on the convex side ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins bind to eIF4E's convex side using their RING domain, which, in contrast to the bond to eIF4G and 4E-BP, decreases the affinity of eIF4E to the cap (Cohen et al, 2001;Kentsis et al, 2001;Volpon et al, 2010). Structural studies show that eIF4E has different conformations and different ligand binding affinities depending on whether it is binding to the cap or not (Niedzwiecka et al, 2002;Niedzwiecka, Darzynkiewicz, & Stolarski, 2004;Volpon et al, 2006;Tomoo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The 4E binding proteins (4E‐BPs), which are major repressors of eIF4E activity, bind at the eIF4G binding site and similarly should not directly block the C‐terminus (Marcotrigiano, Gingras, Sonenberg, & Burley, 1999; Tomoo et al, 2005). The C‐terminus of eIF4E is part of the cap‐binding pocket and is deflected, but not occluded, by binding to mRNA (Marcotrigiano, Gingras, Sonenberg, & Burley, 1997; Tomoo et al, 2002). The C‐terminus of eIF4G, meanwhile, does not bind the protein's other major binding partner, eIF4A, and appears to be modulatory (Morino et al, 2000).…”
Section: Resultsmentioning
confidence: 99%